Historias de la debacle y la migración en el imaginario fílmico argentino-español - Susana Schmidt (Les Cahiers ALHIM)
In the 2001 Argentina, different film directors linked, in their fictional movies, crisis to emigration of Argentines abroad, looking for better opportunities. Assuming some of these movies, generally Argentine-Spanish co-productions, as object of investigation (Lugares comunes, El abrazo partido, Bar “El Chino”, Luna de Avellaneda), we first examine this relation between crisis and migration. Secondly, we raise the representation of migration itself, focused from the perspective of those who stayed in Argentina. Finally, we analyse the significance in the film imaginary of the memory of European immigration.